Boundary element simulation of heat conduction in functionally graded solids - Choo, Wee Kuang. (2013)
The uses of functionally graded solids in the world have risen throughout the years. These solids, made up of functionally graded material (FGM), have changing material properties over space. Therefore, FGM give engineers a wide range of choices and some degree of flexibility in material selection to suit their needs. Although these solids are highly useful, the cost of producing them is fairly expensive.